TRANSFORMASI PEMBAGIAN WARIS ANTARA LAKI LAKI DAN PEREMPUAN PERSPEKTIF MUHAMMAD SYAHRUR (STUDI BUKU TEORI LIMIT) - Asrafi, Moh Firman Asrafi; Wulan, Yunita Wulandari (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2025)
In the last decade, there has been a significant transformation in gender perception regarding inheritance in Islam. Legal reforms have provided fairer rights for women, driven by injustices, changing gender roles, feminism, and human rights. The distribution of inheritance in Islam was previously set at a 2:1 ratio between men and women, with greater obligations placed on men. This research explores the development of inheritance distribution between genders, not in general terms, but through the perspective of Muhammad Syahrur with a focus on the theoretical model of limits. Traditionally, Islamic inheritance law establishes an unequal share, often giving men twice what is given to women, a gap justified by the economic burden placed on men to support their families. This study aims to examine the applicable Islamic inheritance laws to achieve equality in inheritance rights between men and women using Muhammad Syahrur's limit theory and its relevance in the present time. Utilizing qualitative methodology, the author gathers data from various sources such as books and articles related to the topic. This research demonstrates that the interpretation of religious texts in their contextual situations can facilitate a more balanced and fair inheritance law, reflecting modern standards of equality and justice. This study contributes to the debate on gender roles in Islamic inheritance law